(untitled) - Kandera, Branislav; Pistansky, Dalimir (Doprava a spoje, 2012)
This article is focused on assessment of exposure cosmic radiation level for crew members, especially in Slovak Republic. Above mentioned facts show really necessity to exactly follow international and national standards and regulations by operators registered in the Slovak republic. Not following those regulations can in the short term saved money for irresponsible operators. But in the long term it can caused serious health injury what can leads to the financial loses caused by the legal proceeding. Air transport impacts the environment and the environment has an impact on the air transport, especially on the individual users of airspace (aircraft crew) when the cosmic radiation is one of the indicators of the impact of air transport on the environment. This article is published as one of the scientific outputs of the project: "Centre of Excellence for Air Transport ITMS 26220120065".